THE PETERSBURG TEXT OF RUSSIAN LITERATURE AND THE VILNIUS TEXT OF LITHUANIAN LITERATURE: ONCE AGAIN ON THE ANALYTICAL VISTA OF VLADIMIR TOPOROV’S CONCEPT - Видугирите, Инга (Literatūra, 2013)
The concept Petersburg text by Toporov is criticized for its mythological essence, for the confusion of the languages of the object and the analysis in its description, and for the very attempt to create a mental space in which one can escape politics and ideology. The point of such critique is that the concept of Petersburg text is a product of the Soviet era and its highly ideologized atmosphere, as well as of the wish of the intellectuals not to participate in it. Nevertheles, there is a range of texts of cities or regions made by analogy with the Petersburg text (e.g., Moscow, Permj, Siberian, Crimean texts) in the recent Russian humanities. In this article, the author makes an attempt to show the actuality of the Toporov’s concept by comparing it with the modern geocritical theory that does not make a strict separation between cities and texts and treats them as transgressive and mobile. On the other hand, it is stated that the concept of Toporov gains its actuality in discussing the text of the city in its relation to the main historical event of the nation, viz. the founding of Petersburg. This thesis could be proved by applying the notion to Vilnius and its literature. The main event of the modern Lithuanian history concerning Vilnius is the fact that it was given over to Lithuania in 1939. It took another 40 years to create the Vilnius text of Lithuanian literature, in which heroes and their stories are inseparable from the city and its history as well as from its topography. This means that Vilnius and its semiotics have been assimilated by Lithuanian culture, and the city has acquired its text.